Glucocorticoid Treatment Leads to Aberrant Ion and Macromolecular Transport in Regenerating Zebrafish Fins - Schmidt, Johannes R.; Geurtzen, Karina; von Bergen, Martin; Schubert, Kristin; Knopf, Franziska (Frontiers in Endocrinology, 2019)
Long-term glucocorticoid administration in patients undergoing immunosuppressive and anti-inflammatory treatment is accompanied by impaired bone formation and increased fracture risk. Furthermore, glucocorticoid treatment can lead to impaired wound healing and altered cell metabolism. Recently, we showed that exposure of zebrafish to the glucocorticoid prednisolone during fin regeneration impacts negatively on the length, bone formation and osteoblast function of the regenerate. The underlying cellular and molecular mechanisms of impairment, however, remain incompletely understood. In order to further elucidate the anti-regenerative effects of continued glucocorticoid exposure on fin tissues, we performed proteome profiling of fin regenerates undergoing prednisolone treatment, in addition to profiling of homeostatic fin tissue and fins undergoing undisturbed regeneration. By using LC-MS (liquid chromatography-mass spectrometry) we identified more than 6,000 proteins across all tissue samples. In agreement with previous reports, fin amputation induces changes in chromatin structure and extracellular matrix (ECM) composition within the tissue. Notably, prednisolone treatment leads to impaired expression of selected ECM components in the fin regenerate. Moreover, the function of ion transporting ATPases and other proteins involved in macromolecule and vesicular transport mechanisms of the cell appears to be altered by prednisolone treatment. In particular, acidification of membrane-enclosed organelles such as lysosomes is inhibited. Taken together, our data indicate that continued synthetic glucocorticoid exposure in zebrafish deteriorates cellular trafficking processes in the regenerating fin, which interferes with appropriate tissue restoration upon injury.